2016
DOI: 10.1007/s00347-015-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Refraktive Veränderungen bei Triple-Descemet-Membran-Endothel-Keratoplastik

Abstract: The observed hyperopic shift was a mean value. A prediction of refraction in the individual cases by means of the available parameters was not possible. In general, the selection of an intraocular lens with a stronger myopic target refraction than that for standard cataract surgery is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Eyes after DMEK are also subject to a hyperopic shift after IOL implantation. However, the change of total corneal refractive power is markedly smaller (about 0.5 D) in DMEK than in DSAEK [42,43].…”
Section: Descemet's Membrane Endothelial Keratoplasty (Dmek)mentioning
confidence: 81%
“…Eyes after DMEK are also subject to a hyperopic shift after IOL implantation. However, the change of total corneal refractive power is markedly smaller (about 0.5 D) in DMEK than in DSAEK [42,43].…”
Section: Descemet's Membrane Endothelial Keratoplasty (Dmek)mentioning
confidence: 81%
“…21,22,24,25,27,33,35,36,38,42 In 8 (27.6%) studies with tomographic analysis, however, there was a statistically significant steepening of posterior corneal topography. 20,21,23,24,39,41,42,46 In a study of 87 pseudophakic eyes undergoing DMEK, Agha et al reported that postoperative changes were mainly observed in the posterior corneal surface, with a statistically significant reduction of posterior corneal astigmatism from 0.59 ± 0.56 D to 0.39 ± 0.27 D. 24 Moreover, the authors observed an increase in the number of eyes exhibiting an against-the-rule astigmatism from 42.8% to 73.6%, although the proportion of eyes with with-the-rule and oblique astigmatism decreased after DMEK. 24 By contrast, the postoperative change in the anterior corneal curvature was inconsistent throughout the literature, with only 2 studies (6.9%) reporting a significant difference, whereas 5 studies (17.2%) did not.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Moreover, in cases of preoperative corneal edema, the increase in corneal hydration of the posterior stroma has been shown to cause a slight decrease in the overall corneal refractive index, which needs to be considered as well. 41 Another way to optimize the IOL power calculation in patients undergoing triple DMEK is to use the refractive shift of the first eye after DMEK as an orientation to predict the refractive shift and optimize the refractive target of the second eye. 26 In fact, it was recently reported that the extent of refractive shift after triple DMEK in the second eye was comparable with that of the first eye (paired analysis: mean difference 0.49 ± 0.43 D).…”
Section: Discussionmentioning
confidence: 99%
“…Ein bekanntes Phänomen nach DMEK stellt die Hyperopisierung um durchschnittlich ca. 0,6 dpt dar [28][29][30][31]. Bei der Wahl der Intraokularlinse für die Triple-DMEK (Kataraktoperation kombiniert mit DMEK) muss dies entsprechend berücksichtigt werden, sodass bspw.…”
Section: Postoperative Komplikationenunclassified